Prep1 regulates angiogenesis through a PGC‐1α‐mediated mechanism. Issue 12 (15th October 2019) - Cimmino, Ilaria; Margheri, Francesca; Prisco, Francesco; Perruolo, Giuseppe; D'Esposito, Vittoria; Laurenzana, Anna; Fibbi, Gabriella; Paciello, Orlando; Doti, Nunzianna; Ruvo, Menotti; Miele, Claudia; Beguinot, Francesco; et al.
Abstract : Angiogenesis depends on a delicate balance between the different transcription factors, and their control should be considered necessary for preventing or treating diseases. Pre‐B‐cell leukemia transcription factor regulating protein 1 (Prep1) is a homeodomain transcription factor that plays a primary role in organogenesis and metabolism. Observations performed in a Prep1 hypomorphic mouse model, expressing 3‐5% of the protein, show an increase of embryonic lethality due, in part, to defects in angiogenesis. In this study, we provide evidence that overexpression of Prep1 in mouse aortic endothelial cells (MAECs) stimulates migration, proliferation, and tube formation. These effects are paralleled by an increase of several proangiogenic factors and by a decrease of the antiangiogenic gene neurogenic locus notch homolog protein 1 (Notch1). Prep1‐mediated angiogenesis involves the activation of the p160 Myb‐binding protein (p160)/peroxisome proliferator‐activated receptor g coactivator 1a (PGC‐1α) pathway. Indeed, Prep1 overexpression increases its binding with p160 and induces a 4‐fold increase of p160 and 70% reduction of PGC‐1α compared with control cells. Incubation of MAECs with a synthetic Prep1(54‐72) peptide, mimicking the Prep1 region involved in the interaction with p160, reverts the proangiogenic effects mediated by Prep1. In addition, Prep1 levels increase by 3.2‐fold during the fibroblast growth factor β (bFGF)‐mediated endothelial colony‐forming cells' activation, whereas Prep1(54‐72) peptide reduces the capability of these cells to generate tubular‐like structures in response to bFGF, suggesting a possible role of Prep1 both in angiogenesis from preexisting vessels and in postnatal vasculogenesis. Finally, Prep1 hypomorphic heterozygous mice, expressing low levels of Prep1, show attenuated placental angiogenesis and vessel formation within Matrigel plugs. All of these observations indicate that Prep1, complexing with p160, decreases PGC‐1α and stimulates angiogenesis.—Cimmino, I., Margheri, F., Prisco, F., Perruolo, G., D'Esposito, V., Laurenzana, A., Fibbi, G., Paciello, O., Doti, N., Ruvo, M., Miele, C., Beguinot, F., Formisano, P., Oriente, F. Prep1 regulates angiogenesis through a PGC‐1α‐mediated mechanism. FASEB J. 33, 13893‐13904 (2019). www.fasebj.org